AGAMA DAN PLURALISME - Firdaus M. Yunus (Islam Futura, 2014)
Ever y religion was born in the middle of the crush of other major religions, and no religion is born apart from the frenetic life of a pluralistic society. Indonesia as a nation that is multi-ethnic, multi-cultural and multi-faith is a necessity that can not be denied by anyone. The existence of these religions are the special challenges faced by their respective faiths, because pluralism was already around us, and no one is likely to be able to turn it down again. In such conditions of tolerance and dialogue between adherents of different religions are the foundations to maintain the integrity of the plural and multicultural religious communities.